Grit as a Predictor of Career Adaptability in Fresh Graduates - Sri Opera Dwi Andini; Dewi Fitriana; Rena Kinnara Arlotas (Universitas Pendidikan Ganesha, 2025)
Career adaptability is needed by fresh graduates to face various job tasks, and be able to adjust to changes and challenges that arise in the world of work. This study aims to determine the relationship between grit and career adaptability in fresh graduates of UIN Imam Bonjol Padang. This study uses a quantitative approach with correlational methods. The population in this study was 1,331 fresh graduates, with a sample size of 279 selected using random sampling technique. The research instrument used was the Career Adapt-Ability Scale (CAAS) developed by Savickas and Porfeli and has been adapted into Indonesian by Sulistiani. The grit scale used in this study was prepared by Duckworth and has been adapted into Indonesian by Priyohadi. The results of hypothesis testing in this study indicate that there is a significant positive relationship between grit and career adaptability in fresh graduates of UIN Imam Bonjol Padang, with the p-value obtained is 0.00 (p < 0.05). This means that by having high grit, fresh graduates are more able to adapt to the challenges of the world of work and do not give up easily in achieving career goals.